2004
DOI: 10.1378/chest.126.3.845
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Noninvasive Positive Pressure Ventilation in the Treatment of Acute Respiratory Failure in Severe Acute Respiratory Syndrome

Abstract: NIPPV was effective in the treatment of ARF in the patients with SARS studied, and its use was safe for health-care workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
154
0
11

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(166 citation statements)
references
References 11 publications
1
154
0
11
Order By: Relevance
“…Subsequently, these passengers could disseminate the infection at their destinations worldwide [14,63]. Urgent protective and therapeutic actions are considered necessary for pH1N1, SARS and TB, which mostly affect immune-compromised populations [8,12,16,47].…”
Section: Risk Of Aerosol Droplet Generation and Infection Spread Withmentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequently, these passengers could disseminate the infection at their destinations worldwide [14,63]. Urgent protective and therapeutic actions are considered necessary for pH1N1, SARS and TB, which mostly affect immune-compromised populations [8,12,16,47].…”
Section: Risk Of Aerosol Droplet Generation and Infection Spread Withmentioning
confidence: 99%
“…Currently, available recommendations are mainly based on published studies and experiences from the first SARS epidemic in 2003 [8,[11][12][13][14][15][16][17]. The pivotal study arguing that NIV poses a high risk for spread of infection is based on the assessment of particle dispersion using an experimental model.…”
Section: Risk Of Aerosol Droplet Generation and Infection Spread Withmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the Toronto experience with SARS, in which some clinicians contracted SARS when a patient was intubated following NIV failure, the use of NIV in these patients was discouraged. 32 Two subsequent observational studies from China, 33,34 however, found no evidence of viral spread to clinicians who took appropriate precautions. In the event of a bird flu pandemic, ventilator resources are likely to be severely strained, and NIV may offer a means of supporting some of the afflicted, mainly those with initial respiratory failure.…”
Section: Niv To Prevent Endotracheal Intubation In Ali/ards Patientsmentioning
confidence: 99%